2013
DOI: 10.1016/j.febslet.2013.01.073
|View full text |Cite
|
Sign up to set email alerts
|

DksA2, a zinc‐independent structural analog of the transcription factor DksA

Abstract: Transcription factor DksA contains a four-Cys Zn2 +-finger motif thought to be responsible for structural integrity and the relative disposition of its domains. Pseudomonas aeruginosa encodes an additional DksA paralog (DksA2) that is expressed selectively under Zn2+ limitation. Although DksA2 does not bind Zn2+, it complements the Escherichia coli dksA deletion and has similar effects on transcription in vitro. In this study, structural and biochemical analyses reveal that DksA2 has a similar fold, domain str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
50
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(51 citation statements)
references
References 29 publications
1
50
0
Order By: Relevance
“…This and previous studies have shown via complementation or transcription experiments that when DksA has a DXXDXA motif at the tip of the CC domain, it functions as a transcriptional regulator (5,15,17,18). Accordingly, DksA activity is lost when the second D in the motif is mutated (14,(17)(18)(19).…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations
“…This and previous studies have shown via complementation or transcription experiments that when DksA has a DXXDXA motif at the tip of the CC domain, it functions as a transcriptional regulator (5,15,17,18). Accordingly, DksA activity is lost when the second D in the motif is mutated (14,(17)(18)(19).…”
Section: Discussionsupporting
confidence: 68%
“…Previous work showed that the aspartates as well as the alanine in the DXXDXA motif are crucial for activity (14,15,17,18). We constructed variants of DksA and SMc00049, modifying the motif, to investigate if we could abolish or establish DksA activity.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The common structure of this class of transcription factors allows them to reach the active site through the secondary channel and modulate the RNAP. Several such secondary channel interactors have been identified to date in bacteria: transcription elongation and fidelity factors GreA and GreB (5-9); two anti-Gre factors, Gfh1 (10,11) and Rnk (12); and the transcription initiation and elongation factor DksA (13)(14)(15)(16) and its analog, DksA2, from Pseudomonas aeruginosa (17), as well as its structural homolog, TraR, often found on conjugative plasmids (18).…”
mentioning
confidence: 99%